1986
DOI: 10.1021/i200034a006
|View full text |Cite
|
Sign up to set email alerts
|

Method for equilibrium-stage calculations in liquid-liquid extraction. Application to countercurrent cascade design for a quaternary system

Abstract: An iteration-free method for equilibrium-stage calculations in multicomponent systems has been developed. The method is based on the interpolation method suggested in this paper which involves the fitting of the solubility surface of two polynomials (one for each phase) and their use together with the experimental tie-line data in order to calculate new equilibrium data. The method has been applied to a quaternary extraction example for the system water-acetone-acetic acid-chloroform at 25 OC. The suggested me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…However, it is obviously difficult to achieve this under laboratory conditions (Ma, 2009 ). Practical experience shows that in the cascade countercurrent extraction experiment, when the number of rows is ~3 N – 2 times of the number of stages, the extraction process will be close to equilibrium and reach a stable concentration value (Ruiz et al, 1986 ). Therefore, under the laboratory conditions, a total of 10 rows were carried out in the cascade extraction simulation experiment, and the raffinate of the 8, 9, and 10th rows was analyzed for As III content, with the results shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is obviously difficult to achieve this under laboratory conditions (Ma, 2009 ). Practical experience shows that in the cascade countercurrent extraction experiment, when the number of rows is ~3 N – 2 times of the number of stages, the extraction process will be close to equilibrium and reach a stable concentration value (Ruiz et al, 1986 ). Therefore, under the laboratory conditions, a total of 10 rows were carried out in the cascade extraction simulation experiment, and the raffinate of the 8, 9, and 10th rows was analyzed for As III content, with the results shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for parameter fitting and adjustment has been discussed elsewhere . As an alternative, the data can also be empirically correlated using a suitable model based on statistics . However, the range of available experimental data often limits the use of such methods for interpolation.…”
Section: Application In Conceptual Designmentioning
confidence: 99%
“…Cruickshank et al proposed a graphical projection method to represent a quaternary LLE phase diagram with one partially miscible pair. This projection has been used in the design of liquid−liquid extraction processes. , Frameworks for the representation of high-D SLE phase diagrams have been developed for nonreactive molecular systems, electrolyte mixtures, and systems involving polymorphs . In these frameworks, a sequence of cuts and projections of the high-D phase diagram is considered, to provide a mental picture of the system in its entirety.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work (Ruiz et al 8 ) we suggested an interpolation method to run the equilibrium stage calculations for liquid-liquid extraction calculations for quaternary systems. The method was named as an iteration-free method and allowed the design of countercurrent cascades.…”
Section: Introductionmentioning
confidence: 99%